An Analysis of Students’ Speaking Ability in Role Playing Dialogues of Guests Handlingat Vocational High School - Ulva Khairani; Rusdi Rusdi; An Fauzia Rozani Syafei (Journal of English Language Teaching, 2017)
This research aims to analyze students‟ speaking ability in role playong “Dialogues of guests handling” viewed from grammatical and lexical features. The design of this research is descriptive research. The populations of this research are the eleventh year of Administrasi Perkantoran students of SMKN 3 Padang. The sample of this research is get by using cluster sampling where the researcher chooses one class, that is XI AP 2 class. Data of this research are students‟ speaking ability in role playing dialogues of guests handling. The data are taken by giving speaking test in which the students are required to role play dialogues of guests handling. The result ot students‟ speaking ability viewed from grammatical features is 71,56 which classified into very good. The result ot students‟ speaking ability viewed from lexical features is 79,01 which classified into very good.